Contratos entre empresas de biodiesel e agricultores familiares de mamona: uma aplicação do modelo principal agente com moral Hazard - Oliveira, Marianne Costa (2009)
The Brazilian government has initiated a policy to support the biodiesel production, developed through the National Programme of Use and Production of Biodiesel (PNPB), which will finally integrate agricultural families into fuel supply. The objective of the research is to analyse the contractual relations which are being formed between Brazil Ecodiesel and agricultural families, especially producers of mammon in the North East region, within the range of PNPB. The logic of the Principal-Agent of Moral Hazard was used to analyse the contract, attempting to solve the problem of asymmetry existing in such a connection and discussing, if the contract encourages families, producers of mammon, and affects the production. The results infer that agricultural families feel attracted to participate in contract and its design at first sight is appropriate to stimulate the efforts. However, other factors besides the contract, for example, questions in structural characteristics of agriculture, can influence that the connection would not be favourable for the parties involved and farmers will end up consolidation of a productive bio diesel network.